صورة المرأة في المسرح الأمريكي والمسرح السوري: تنسي وليامز وسعد الله ونوس أنموذجان (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This paper aims at studying the female presentations in the dramas of two contrasting cultures in America and Syria.   Female characters are sometimes - in varying degrees- conceived very similarly in the dramas of Tennessee Williams (1914-1983) and Sa'dallah Wannus (1941- 1997).  Some examples depart from this generalization. Despite  cultural and personal differences between them,Williams and Wannus are surprisingly similar in the way they dramatized women.  Both writers are concerned about the lost land and culture,the American south in Williams and Palestine in Wannus.  In both cases it is women who mourn the loss and suffer as consequence. Both playwrights were brought up in societies that had similar notions of masculinity, femininity and sexual morality. Women in the works of both writers do not conform to the stereotypes prescribed by the society   Moreover, both wrote compulsively for the stage as they were under the threat of impending death. Williams was a hypochondriac who was convinced that he had cancer and heart condition, while Wannus was bravely fighting cancer in the last few most prolific years of his life Both writers sympathized to a great extent with their heroines and were fascinated with sexually active female characters.  Women in the plays of both dramatists have great desires and have conflict between body and soul.  They undergo a repressive upbringing and rebel against it in a Lawrencean manner.  Their excessive desire is more akin to that of men.   Such female characters are empowered in various ways and assume reversed gender roles  The most outstanding meeting point between both writers is that both upset the traditional notions of masculinity and femininity familiar to their backgrounds. يهدف البحث إلى دراسة صورة المرأة في المسرح في تقافتين متباينتين في أمريكا وسوريا ونأخذ تحديداً الأعمال المسرحية للكاتبين تنسي وليامز (1914-1983) وسعد الله ونوس (1941-1997) على الرغم من التمايز الثقافي والشخصي بين الكاتبين فإن وليامز وونوس متشابهان في الطريقة التي أبرزا فيها المرأة  كان كلا الكاتبين متأثر بضياع الأرض والتشوه الحضاري الناتج عن فقدان الجنوب الأمريكي في حالة وليامز وفلسطين في حالة ونوس. وفي كلتا الحالتين كانت المرأة هي التي تحزن حداداً على الوطن وتعاني على المنصة بأشكال شتى. لقد نشأ الكاتبان في مجتمعين متشابهين في نظرتهما إلى الأنوثة والذكورة والتربية الجنسية وظهرت النساء في أعمال الكاتبين ثائرة على القوالب الجاهزة التي تزج بها عموماً. تعاطف كلا الكاتبين مع بطلاتهما إلى حد بعيد وقد افتتنا بشخصية الأنثى الناشطة جنسياً.  فالشخصيات النسائية في إرث كلا الكاتبين تنطوي على رغبة أسطورية وتعاني من صراع بين الجسد والروح. تمر هذه المرأة  بطفولة يسيطر عليها الكبت ثم تتمرد وتثور بشكل مماثل لشخصيات دي اتش لورنس. وغالباً ما تتخذ هذه النساء الثائرات أدوارا قوية وفاعلة  تنسب عموماً للجنس الآخر. تتجلى  نقطة الالتقاء بين الكاتبين في الطريقة التي قلبا فيها المفهوم التقليدي للذكورة والأنوثة رأساً على عقب .